Poetics Then and Now - Kostkiewiczowa, Teresa (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
The meaning of the word “poetics,” as derived from Aristotle’s understanding given in Poetics, points to the ways of creating verbal works, their components and connections as well as the formation of utterances. Poetics presents a fundamental set of terms referring to a literary work, which are still used and, in fact, are indispensable in all areas of contemporary literary, as well as cultural studies. Due to the changes in the field of literature itself, this set of terms and notions is constantly being updated, and it is still open in terms of both its components and their senses. It constitutes a conceptual framework, some elements of which are universal and operational in nature, and some connected with a particular cognitive horizon and a certain way of perceiving and understanding literature. Poetics is not a permanent theoretical model of literariness, nor is it a set of instructions determining the interpretation of a literary work. It aims at establishing certain testable tools which are indispensable not only in literary studies, but also in studying all other forms having a semiotic content (intersemiotic poetics). For this reason, certain basic terms and notions applied in poetics can be seen as important epistemological categories through which the human mind perceives the world.
Translated by Edyta Więcławska.
Keywords: poetics; literary theory; literary terms; Aristotle’s Poetics